TiO2 Macroscopic Fibers Bearing Outstanding Photocatalytic Properties Obtained through an Integrative Chemistry-Based Scale-Up Semi-Industrial Process. Issue 1804 (2015) - Kinadjian, Natacha; le Bechec, Mickael; Neri, Wilfrid; Poulin, Philippe; Lacombe, Sylvie; Backov, Rénal
ABSTRACT: In here we depict the morphogenesis and associated properties of TiO2 -based macroscopic fibers designed for the photodecomposition of volatile organic compounds (VOC). We employed a continuous industrially scalable extrusion-based process making the use of hybrid sols of amorphous titania nanoparticles, polyvinyl alcohol (PVA) and occasionally latex nanoparticles. This process allowed for the continuous generation of hybrid TiO2 /latex/PVA or TiO2 /PVA macroscopic fibers. Upon thermal treatment, biphasic porous fibers are obtained containing the anatase phase of TiO2 with 10-15% of brookite. These fibers, which can be manufactured under several hundred meter of length, are offering significantly improved phototocatalytic efficiency now comparable to the commercial Quartzel®PCO photocatalyst for gas-phase acetone mineralization.